2020
DOI: 10.1021/acsaem.0c01154
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Water Splitting Photoelectrocatalysts Using Flexible Organometallic Complex and Nanographene Multilayer Thin Films

Abstract: In comparison with conventional inorganic photocatalysts, organic photoactive materials are promising photocatalysts owing to their high extinction coefficient and chemical tunability. However, their limited photocatalytic activity, induced by a low relative permittivity with high recombination energy, poses significant challenges. Herein, a highly efficient bifunctional photocatalytic hybrid multilayer electrode is designed by a versatile layer-by-layer (LbL) assembly of nanoscale graphene oxide (nGO) and a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Overall, the average lifetime calculated is 213 ns, a value shorter than that of the [Ru(dqpCOOH) 2 ] 2+ complex in both deaerated (2.55 μs) and air-equilibrated acetonitrile (314 ns), also denoting the quenching process. 29 Interestingly, the long component recorded on rGO appears more extended than that in air-equilibrated solution, which might reflect the relatively high rigidity of the ruthenium complexes once grafted on the rGO surface. In addition, the appearance of two decay components could be an indication of different populations of Ru 2+ complex, which present different sensitivity toward the quenching of rGO.…”
Section: Materials Characterizationmentioning
confidence: 97%
See 1 more Smart Citation
“…Overall, the average lifetime calculated is 213 ns, a value shorter than that of the [Ru(dqpCOOH) 2 ] 2+ complex in both deaerated (2.55 μs) and air-equilibrated acetonitrile (314 ns), also denoting the quenching process. 29 Interestingly, the long component recorded on rGO appears more extended than that in air-equilibrated solution, which might reflect the relatively high rigidity of the ruthenium complexes once grafted on the rGO surface. In addition, the appearance of two decay components could be an indication of different populations of Ru 2+ complex, which present different sensitivity toward the quenching of rGO.…”
Section: Materials Characterizationmentioning
confidence: 97%
“…[Ru­(tpy) 2 ] 2+ complexes likely because the strain induced by the bite angle of the tridentate ligand promotes radiationless decay and population of 3 MC states leading to a comparatively very short lifetime of their excited state, limiting their potential and applicability in photocatalysis . In this regard, the recent incorporation of [Ru­(tpy) 2 ] 2+ complexes into photoactive materials has shown promising enhancement of the hybrid materials’ photocatalytic performance. , Wilhelm and co-workers showed significantly improved photocatalytic activity when anchoring a [Ru­(tpy) 2 ] 2+ complex onto graphene oxide (GO) …”
Section: Introductionmentioning
confidence: 99%
“…Recently, a tandem cell comprising of an n-type photoanode of n-Se/BiVO 4 and a p-type photocathode of p-Cr 2 O 3 /CuO:Ni could reach a photocurrent of ≈0.04 mA cm −2 at zero bias. [500] Kim et al [501] demonstrated a unique, flexible, and hybrid bifunctional multilayer PEC water splitting photoelectrode composed of nanoscale graphene oxide (nGO) and a terpyridine complex of ruthenium(II) (TPY 2 Ru) on an ITO-coated PET substrate for overall water splitting reaction. To make an efficient PEC system for water splitting, they hosted a TPY 2 Ru to harvest visible light to create more photoinduced electrons as well as nGO to afford photoactive sites for water splitting in the multilayer photoelectrode.…”
Section: Binder-free Electrodes For Bifunctional Solar Photoelectroch...mentioning
confidence: 99%
“…During the past several decades, metal–organic complexes have attracted great attention. By virtue of unique physical and chemical properties, these complexes show great application potential in various areas, such as in energy, [ 22,23 ] catalysis, [ 24,25 ] biomedicine, [ 26 ] and environment treatment. [ 27,28 ] For example, Gorla et al.…”
Section: Introductionmentioning
confidence: 99%